SISTEM POINT OF SALES (POS) DENGAN PENERAPAN MODEL WATERFALL PADA TOKO NINGNONG CIPUTAT (Studi Kasus : TOKO NINGNONG CIPUTAT TANGERANG SELATAN) - Maulana Nurul Hidayat; Susanna Dwi Yulianti Kusuma (CV. Multi Kreasi Media, 2022)
Sales is an integrated effort to develop a strategic plan that is directed at satisfying the needs and desires of buyers to get sales that generate profits (Marwan A, 1986). Sale is a transfer of rights to objects. From this explanation, working in transferring or transferring goods and services requires people who are in the field of sales such as trade operations, agents, service representatives, and marketing representatives. From the above understanding that the lifeblood of a merchant's business, especially the